Correction: Ambient and household PM2.5 pollution and adverse perinatal outcomes: A meta-regression and analysis of attributable global burden for 204 countries and territories. - Rakesh Ghosh (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pmed.1003718.].